2011
DOI: 10.1111/j.1751-7133.2011.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid as a Predictor of All-Cause Mortality in Heart Failure: A Meta-Analysis

Abstract: Serum uric acid (SUA) is a product of xanthine oxidase (XO). Apoptosis and tissue hypoxia lead to increased purine catabolism, which, in turn, increases XO activity and subsequently SUA levels. The purpose of this study was to perform a meta-analysis to evaluate the evidence supporting SUA as a predictor of all-cause mortality in patients with heart failure (HF) and to determine the SUA cut-off for the increase in risk. A search of the MEDLINE database (1966 to March 2009) supplemented by manual searches of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 23 publications
5
95
0
14
Order By: Relevance
“…In addition, the prognostic role of serum uric acid (UA) has been established in patients with chronic HF 10, 11, 12, 13. In a recent investigation in patients with acute HF, admission hyperuricemia was shown to be associated with higher risk of death or HF rehospitalization at 6 months 14…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prognostic role of serum uric acid (UA) has been established in patients with chronic HF 10, 11, 12, 13. In a recent investigation in patients with acute HF, admission hyperuricemia was shown to be associated with higher risk of death or HF rehospitalization at 6 months 14…”
Section: Introductionmentioning
confidence: 99%
“…6 In a metaanalysis, hyperuricaemia was associated with high all-cause mortality in HF patients. 7 Furthermore, a recent study demonstrated that hyperuricaemia was associated with increased all-cause mortality in patients who were hospitalised for HFpEF. 8 However, the association between UA and DD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of SUA on all-cause mortality at different SUA cut-offs in CHF patient population was evaluated using meta-regression. There was a linear association between SUA after 7 mg/dL and mortality [23]. Arguing against a pure protective role of SUA in cardiovascular disease [24], we found that levels of SUA remained independently associated with lowed proangiogenic MPCs after adjusting for parameters with known impact on concentrations of MPCs.…”
Section: Discussionmentioning
confidence: 54%
“…Probably, these findings might be taken into consideration to be explaining controversial role of SUA in CHF evolution and outcomes. Really, significant association between high SUA level and BMI, diuretic use, some biomarkers, such as NT-pro-BNP, as wells as with hemodynamic performances (E/Ea and LVEF) even beyond declining eGFR was frequently noted in recent investigations [23,25]. Amin et al [26] reported that mild elevated SUA levels in patients with systolic CHF is associated with impaired clinical and hemodynamic profile and might be used as a noninvasive indicator of elevated left ventricular filling pressures.…”
Section: Discussionmentioning
confidence: 99%